Synthesis and Antibacterial Activity of Pyrazolo[1,5-a]quinazoline-3-carbonitriles - Nazeer, Areesha; Perveen, Najma; Ain Khan, Misbahul; Naeem Khan, Muhammad; Ali Munawar, Munawar; Lin, Whei-Oh (Asian Journal of Chemistry, 2013)
A method for the synthesis of 4,5,6,7,8,9-hexahydro-5-arylpyrazolo[1,5-a]quinazoline-3-carbonitriles was developed. 5-Aminopyrazole-4-carbonitrile when reacted with aromatic aldehydes gives the schiff's base which on cyclization with cyclohexanone in the presence of glacial acetic acid produces a series of title compounds. The synthesized compounds were characterized through elemental analysis and spectroscopic techniques (FTIR, 1H NMR and MS). The antibacterial activity of these compounds was also tested against six different bacterial strains by agar plate disc method.